Майоліка на фасадах львівських споруд у стилі «піттореск»: типологічний та композиційний аналіз - Казанцева, Т. (Студії мистецтвознавчі, 2009)
The author has carried majolica natural investigations on 38 L’viv buildings facades in the “picturesque” style. According to the investigations results it has been made the table that contains information about building address, its former destination and the date of construction, features of majolica location and its description. The treatment of investigation materials gave author the possibility to work out majolica types and analyze their composition and stylistic. Usually majolica has been combined with brick and stucco architectural decoration of the neo–styles of the end of the 19th century. Majolica assortment has been collected from monolith elements (stars, roses, coat of arms and medallions) and square tiles. The last ones have been divided into two groups. The ornaments “bandelwerk” and arabesque have been collected from the first tiles group. The second tiles group have got closed composition, in the centre of which the palmetto or trefoil regularly have been located. Sometimes tiles have been decorated with concentric circles, rustic imitation or rose’s variety. Panels, rectangle frames, friezes, eight–pointed stars and rhombic compositions have been made up from ceramic tiles. Frequently single tiles and compositions from them have been decorated by brick frame. Besides several exceptions majolica of the “picturesque” style is relief that caused the surface pollution and coloristic distortion. The cleaning by author of several tiles made possible to detect authentic colors: orange, blue, green and brown against white background. Besides of the surface pollution another actual problem is majolica cracking and upper layer exfoliation caused by frosting and melting processes.